Penerapan Model Pembelajaran Student Facilitator and Explaining Berbantuan Media Papan Buletin untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas IV SDN-2 Langkai Palangka Raya Tahun Pelajaran 2016/2017: Application of Student Facilitator Learning Model and Explaining the Assistance of Media Bulletin Boards to Improve Science Learning Outcomes of Grade IV Students of Palangka Raya's SDN-2 Langkai Academic Year 2016/2017 - Mayang Analia; Muhamad Ramli (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to: (1) Describe the activities of Mathematics learning in fourth grade students of Langkai Palangka Raya SDN-2 2016/2017 Academic Year on the application of Student Facilitator and Explaining models assisted by Bulletin Board media, (2) Improve science learning outcomes of fourth grade students in the Langkai Palangka Raya SDN-2 2016/2017 Academic Year after the application of the Student Facilitator and Explaining models assisted by the Bulletin Board media. The type of research used by researchers was Classroom Action Research (PTK) with the research subjects of all fourth-grade students in the Langkai Palangka Raya SDN-2, totaling 15 students consisting of 9 men and six women. Data collection techniques in this study used observation and tests. Data analysis uses qualitative and quantitative data analysts. The results of this study indicate that: (1) Activity of Grade IV students of SDN-2 Langkai Palangka Raya in the academic year 2016/2017 in science learning after applying Student Facilitator and Explaining models assisted by Bulletin Board media to be good, because students are active, enthusiastic, listening teacher explanation and enthusiasm in following the learning process. The results of the observations of teacher activities on teaching and learning activities carried out by observer I and observer II during the learning process of science in the first cycle the universal aspect of teacher activity 3.50 in the category is excellent, and the global element of students is 3.59 in the group very good. (2) There is an increase in science learning outcomes by applying the Student Facilitator and Explaining model assisted by Bulletin Board media in grade IV science subjects at the Langkai Palangka Raya Elementary School 2 in the academic year 2016/2017. This is indicated by the learning outcomes seen through the class average in cycle I which is equal to 85.33, and the completeness percentage of students in classical is 93.33%, from the predetermined provisions namely for KKM of 70 and completeness criteria in traditional 85 %.